Kedudukan Hukum Tata Usaha Negara Dalam Penyelesaian Sengketa Terhadap Putusan Pemberhentian Tidak Hormat - Dodi Togatorop (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Indonesia as a developing country is currently developing in various sectors. Globalization is a process of organizational change in relation to the functioning of capitalism, which is characterized by the emergence of market integration and transnational corporations, as well as the underdevelopment of supranational institutions. Thus, it is possible to influence the work behavior of the Indonesian people, so that if the party who feels aggrieved is not satisfied with the results of dispute resolution due to the development of globalization, an appeal is needed. . The appeal as referred to in is an administrative action based on Article 48 of Law Number 51 of 2009 concerning Amendments to Law Number 9 of 2004 concerning Amendments to Law Number 5 of 1986 concerning State Administrative Courts (PTUN). The purpose of the wording of this Article is to know the authority of the State Administrative Court in resolving state administrative disputes against dishonorable dismissal decisions and the steps that must be taken to resolve them as state administrative disputes. The research method applied is normative-law. The settlement of labor disputes is resolved by the State Administrative Court, except for labor disputes due to violations of the disciplinary code of the state civil apparatus, which are resolved by administrative complaints to the Personnel Advisory Board. ,